DIGITAL LITERACY LEVEL OF ELEMENTARY SCHOOL STUDENTS: A DESCRIPTIVE QUANTITATIVE STUDY - Fithri Nurlaelasari; Wahyu Sopandi; Rina Heryani; Angga Hadiapurwa (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
Digital literacy is a crucial competency for Generation Alpha students growing up in an increasingly complex digital environment. Although elementary school students are now intensively exposed to technology from an early age, their digital literacy levels have not yet developed optimally across all dimensions, and the contextual factors that shape their profile differences, such as grade level, age, gender, and device ownership, are not yet empirically understood. This study aims to analyze the digital literacy levels of upper-grade students at a public elementary school in Cimahi City, based on the four pillars of digital literacy, and to compare their profiles across these contextual variables. A quantitative descriptive survey was conducted with 150 students through purposive sampling, using a 20-item questionnaire adapted from the Ministry of Communication and Digital Development (Kemkomdigi) framework (2025). The results showed an overall achievement of 83.56% (Good category), with the highest digital security (90.59%) and the lowest digital skills (74.52%). There is a consistent upward trend across grade (79.71%–85.87%) and age (76.67%–85.17%), with minimal gender differences, and students with their own devices outperformed those using parental devices on the digital skills and safety pillar. The gap between high levels of ethical awareness and digital safety on the one hand and low levels of productive skills on the other hand indicates that technology exposure has not been optimally directed in the learning context. These findings indicate the need for targeted interventions to strengthen elementary school students' productive digital competencies.